Pengembangan Nugget Berbasis Ikan Lele dan Daun Kelor Sebagai Pencegahan Anemia - Fathia Ihza Ramadhani; Fitriana Mustikaningrum (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2026)
One of the problems that occur in pregnant women is anemia. Prevention of anemia in pregnant women, apart from consuming iron tablets, is by consuming additional foods such as processed local foods made from catfish and moringa leaf flour. This study aims to determine the nutritional value, physicochemical tests, acceptability, and food cost of LeKer nuggets. The experimental research method used a completely randomized design. Only two formulas were used with two repetitions. The study was conducted at the Laboratory of Muhammadiyah University Surakarta. All data were first tested for normality, then analyzed using the Independent T-test if normally distributed and the Mann-Whitney test if not normally distributed. The results of this study showed no significant difference in moisture content (p=0.169). There was no significant difference in oil absorption (p=0.372), while there was a significant difference in overall acceptability of the nuggets (p=0.002). The conclusion of this study is that there was no significant difference in moisture content and oil absorption, while the acceptability preferred by the panelists was found in formula 1.